Effects of thermal intermittence on fruit characteristics and drying time in convective drying of mango (Mangifera indica L.) - Amado, L. R. [UNESP]; Silva, K. S.; Mauro, M. A. [UNESP]; Carcel, J. A.; Clemente, G.; GarciaPerez, J. V.; Mulet, A.; Rossello, C. (Univ Politecnica Valencia, 2018)
This study investigated the influence of the intermittent drying conditions on drying kinetics and on color and carotenoid retention of mangoes. The drying conditions were 95 degrees C (40 min) and 80 degrees C (40 min) in the first stage combined with 70 degrees C and 60 degrees C in the second stage, and continuous drying (70 degrees C and 60 degrees C) as control. Drying time was reduced by thermal intermittence and carotenoid retention was more affected by temperature than drying time. The results also highlighted the carotenoid sensitivity to 70 degrees C temperature, showing the importance of limiting the temperature of the mango to 60 degrees C during the two drying stages.
Keywords: Intermittent drying; thermal intermittence; carotenoid; color